Secondary skull tumors: Prevalence, MRI findings as a diagnostic tool, and treatment - Flamerz, Bassam Mahmood (AL-Kindy College Medical Journal, 2016)
Background: Skull secondary tumors are malignant bone tumors which are increasing in incidence.Objective: The objectives of this study were to present clinical features , asses the outcome of patients with secondary skull tumors ,characterize the MRI features, locations, and extent of secondary skull tumors to determine the frequency of the symptomatic disease.Type of the study: This is a prospective study.Methods: This is a prospective study from February 2000 to February 2008. The patients were selected from five neurosurgical centers and one oncology hospital in Baghdad/Iraq. The inclusion criteria were MRI study of the head(either as an initial radiological study or following head CT scan when secondary brain tumor is suspected , visible or palpabable skull mass is noted ) that revealed either calvarial or skull base metastases were included in this study.Results: During the period of the study 175 patients were included according the inclusion criteria. Primary sites were breast cancer (54.85%), lung cancer (14.28%), prostate cancer (6.28%), malignant lymphoma (5.14%), and others (19.42%). The mean time from primary diagnosis to skull metastasis diagnosis was 71 months for cases of breast cancer, 26 months for prostate cancer, 9 months for lung cancer, and 4 months for malignant lymphoma. Calvarial circumscribed intraosseous metastases were found most frequently (25.7%). The patients were mainly asymptomatic. However, some patients suffered from local pain or cranial nerve palsies that harmed their quality of life. Treatment, mainly for symptomatic cases, was by local or whole-skull irradiation.Conclusion: Secondary skull tumors are not rare, and most are calvarial circumscribed intraosseous tumors. MRI contribute to understanding their type, location, and multiplicity, and their relationship to the brain, cranial nerves, and dural sinuses. Radiation therapy improved the quality of life (QOL) of patients with neurological symptoms.